Teknologi Tepat Guna Bagi Kelompok Penjual Bunga Segar - Sandra Oktaviana Pinaraswati; Totok Hendarto (STIE Malangkucecwara, 2018)
The business of selling fresh flowers is a quite profitable business, because interest is needed for many events. Flower selling business problems include the fields of production, management and marketing. The solution to problem solving from priority scale is: Creating appropriate technology design in the form of adequate sales window. Manfaan and purpose of making this flower display or tool: able to maintain the freshness of flowers, slow down the fading color of flowers, able to maintain the original scent of flowers and minimize the level of damage and loss of interest due to wind. Conclusion in the production field. and the brightness of the flowers and the level of damage has decreased. The management field has had a positive impact on the fresh flower sales program. The marketing sector as a whole also has a positive impact on the fresh flower sales program.